Pengaruh Pijat Oksitosin terhadap Produksi ASI pada Ibu Post Sectio Cesarea - Susianti, Susianti; Usman, Arifa (Poltekkes Kemenkes Palu, 2019)
Oxytocin massage is performed to stimulate the oxytocin reflex or let down reflex. By doing this massage, the mother will feel relaxed, so that the hormone oxytocin comes out the breast milk quickly. The purpose of this study was to determine the effect of oxytocin massage on breast milk production in post sectio secarea mothers. This research method used a quasi-experimental method (Quasi Experiment) with Post Test Only design with control group design. The sampling technique with non-probability sampling was consecutive sampling with the number of respondents as many as 50 samples, namely 25 samples for the intervention group and 25 people with the control group. Data analysis applied the Chi-Square test. The results of the bivariate analysis showed that the p-value in each measurement was 0.039, 0.003, 0.002, which means that there were differences in the proportions of the smoothness of breast milk in the intervention group and the control group. Conclusion: There is a difference in the proportion of smoothness of breast milk in the intervention group and the control group, and there is no relationship between oxytocin massage with age, education, occupation, and parity.